A review of medical and surgical management of ectopic Pregnancy in Al Wakra Hospital - Zeena Martis (17039087) (2023)
Introduction An ectopic pregnancy is a major cause of maternal morbidity in the short and long term. We propose a descriptive review to highlight management among all patients admitted to AWH with ectopic pregnancy. Objectives To determine the ethnicity of patients diagnosed with ectopic pregnancy. To assess the successful rate of medical and surgical management between these patients. Retrospective chart review from medical records. Methods A retrospective chart review of 156 patients who are admitted in inpatient obs/ gyn unit with ectopic pregnancy were reviewed. Demographic data, ethinicity, treatment and outcomes were analyzed using a excel sheet. Results 156 cases of ectopic pregnancy were admitted in patient obs/gyn department in Al wakra hospital- HMC, Qatar during the period Jan 2020 till Nov. 2022. Patients were classified into two categories based on their management: either medically managed with methotrexate, or surgically. We found that the success rate in patients received one dose of methotrexate was (84%). The success rate of second dose of methotrexate was (6.4%); However (9.6%) went for surgical management due to rupture ectopic or ß-hCG level was more than 5000 IU. In terms of ethnicity, our review showed that the higher proportion of ectopic was seen in the Asian region (65%) compared to 26% in the African region and 9% in the other region. Among them, 36% speak Arabic, and 5% are Qatari. Conclusion Medical management with Methotrexate remains a very effective modality of treatment for ectopic pregnancy. Early identifying of underlying risk factors, diagnosis with the essential aids like transvaginal ultrasound and β-hCG and timely intervention in the form of medical or surgical treatment will definitely help in reducing the morbidity and mortality associated with ectopic pregnancy and to improve the future reproductive outcome.